A Re-Examination of the Relationship between Foreign Flows and Economic Growth in LLDCs: Dynamic Fixed Effects (DFE) - Quadri, Faruq Umar (Asian Journal of Economics and Empirical Research, 2019)
There are 32 landlocked developing countries (LLDCs) across four major continents of the world. These countries are mostly low-income or lower middle-income developing economies and suffer from a number of challenges especially, dwindling economic growth. The main objective of the study therefore, is to re-examine how economic growth in LLDCs can be influenced with the aids of foreign flows such as foreign direct investment (FDI), foreign portfolio investment (FPI) and official development assistance (ODA). The study made use of a sample of 19 member-states due to data limitation in order to evaluate the impact of foreign flows on economic growth using ARDL panel approach with the Dynamic Fixed effect (DFE) as the baseline estimation techniques during the period of 1995 to 2017. Our finding reveals that in the long-run, net FDI and net ODA have impacts on the economic growth in LLDCs but net FPI shows no any discernible impacts on GDP growth in LLDCs.